2019
DOI: 10.20473/fmi.v55i3.15501
|View full text |Cite
|
Sign up to set email alerts
|

Human Sperm Motility, Viability, and Morphology Decreased after Cryopreservation

Abstract: The aim of this study was to analyze human sperm motility, viability, and morphology before and after cryopreservation. This true laboratory experimental study had pre and post randomized one group design. The study was conducted at the Embryology, Andrology, and Genetics Laboratory, Department of Medical Biology, Faculty of Medicine, Universitas Airlangga from August to November 2017. The eighteen samples of fresh semen were collected from male volunteers who agreed and signed the informed consent of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The inevitable change involves the significant reduction in motility mostly due to membrane changes and acrosome degeneration among the others. A decrease in spermatozoa kinetics after thawing has been reported consistently in many studies [26][27][28][29].…”
Section: Changes In Sperm Parameters During Cryopreservationmentioning
confidence: 69%
See 1 more Smart Citation
“…The inevitable change involves the significant reduction in motility mostly due to membrane changes and acrosome degeneration among the others. A decrease in spermatozoa kinetics after thawing has been reported consistently in many studies [26][27][28][29].…”
Section: Changes In Sperm Parameters During Cryopreservationmentioning
confidence: 69%
“…Another parameter affected by freezing is sperm morphology which mostly results due to the deformation in membrane structure due to dysregulated liquid influx [2,7,27,29]. It has also been shown that freeze preservation of sperm is followed by ultrastructural changes [11].…”
Section: Changes In Sperm Parameters During Cryopreservationmentioning
confidence: 99%
“…There are two types of cryoprotectants: extracellular and intracellular. Extracellular cryoprotectants protect the cell membrane from the osmotic pressure created by freezing; one of these agents is sugar (Darsini et al 2019). Osmotic stress can cause structural changes in sperm, altering sperm morphology (Yeste et al 2017).…”
Section: Quality Of Fresh Kub Semen Quality With Different Phenotypementioning
confidence: 99%
“…The produced sperm are transferred to another tube, called the epididymis, where they are stored [2]. Male infertility depends on various parameters, such as the number, motility, viability, and morphology of the sperms, which are affected by several factors [3]. There are several reasons for insufficient blood supply to testicular tissue, which causes hypoxia and oxidative stress [4].…”
Section: Introductionmentioning
confidence: 99%